2007
DOI: 10.4049/jimmunol.179.10.6620
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 IFN Mediates Cross-Talk between Innate and Adaptive Immunity That Abrogates Transplantation Tolerance

Abstract: TLR activation of innate immunity prevents the induction of transplantation tolerance and shortens skin allograft survival in mice treated with costimulation blockade. The mechanism by which TLR signaling mediates this effect has not been clear. We now report that administration of the TLR agonists LPS (TLR4) or polyinosinic:polycytidylic acid (TLR3) to mice treated with costimulation blockade prevents alloreactive CD8+ T cell deletion, primes alloreactive CTLs, and shortens allograft survival. The TLR4- and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 57 publications
(87 reference statements)
1
66
1
1
Order By: Relevance
“…Recently, type I IFNs have been reported to mediate the prevention of skin allograft acceptance by LPS and polyinosinic:polycytidylic acid by reducing the deletion of alloreactive CD8 ϩ T cells necessary for graft acceptance (42). We have extended these findings to a microbial infection and demonstrate a correlation between LM-induced IFN-␤ production and the prevention of allograft acceptance, the necessity of IFN␣R1 signaling for LM to prevent anti-CD154/DST-induced graft survival, and the sufficiency of type I IFN to prevent anti-CD154/ DST-mediated graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, type I IFNs have been reported to mediate the prevention of skin allograft acceptance by LPS and polyinosinic:polycytidylic acid by reducing the deletion of alloreactive CD8 ϩ T cells necessary for graft acceptance (42). We have extended these findings to a microbial infection and demonstrate a correlation between LM-induced IFN-␤ production and the prevention of allograft acceptance, the necessity of IFN␣R1 signaling for LM to prevent anti-CD154/DST-induced graft survival, and the sufficiency of type I IFN to prevent anti-CD154/ DST-mediated graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 These adjuvants include agonists of Toll-like receptors 3 and 4, which might induce antigen-independent activation and maturation of B cells and T cells. 4,5 Most patients in the study by Scharpé and colleagues were on relatively conventional immunosuppression regimens consisting of a calcineurin inhibitor (tacrolimus or ciclosporin), an antiproliferative agent (azathioprine or mycophenolate mofetil) and a corticosteroid (methylprednisolone). Patients on newer immunosuppressive agents, such as sirolimus, alemtuzumab or belatacept, and those on protocols that avoid steroids or calcineurin inhibitors, might have markedly different vaccine responses and adverse effect rates.…”
Section: O M M E N Ta Rymentioning
confidence: 98%
“…45,46 Furthermore, in studies in both patients and experimental models in which tolerance has been achieved investigators have demonstrated that type I-IFN signaling after either viral infection or endogenous administration can initiate rejection. 47,48 Conversely, type I-IFN blockage in conjunction with immunosuppression can prolong allograft survival. 49 Therefore, although the role of type I-IFN after solid-organ transplantation still remains controversial, a majority of studies suggest that signaling enhances alloreactive responses.…”
mentioning
confidence: 99%